Encapsulation of Human Natural and Induced Regulatory T‐Cells in IL‐2 and CCL1 Supplemented Alginate‐GelMA Hydrogel for 3D Bioprinting. (20th February 2020) - Kim, Juewan; Hope, Christopher M.; Gantumur, Narangerel; Perkins, Griffith B.; Stead, Sebastian O.; Yue, Zhilian; Liu, Xiao; Asua, Ane U.; Kette, Francis D.; Penko, Daniella; Drogemuller, Christopher J.; Carroll, Robert P.; et al.
Abstract: Regulatory T‐cells (Tregs) are important modulators of the immune system through their intrinsic suppressive functions. Systemic adoptive transfer of ex vivo expanded Tregs has been extensively investigated for allogeneic transplantation. Due to the time‐consuming and costly expansion protocols of Tregs, more targeted approaches could be beneficial. The encapsulation of human natural and induced Tregs for localized immunosuppression is described for the first time. Tregs encapsulated in alginate‐gelatin methacryloyl hydrogel remain viable, phenotypically stable, functional, and confined in the structure. Supplementation of the hydrogel with the Treg‐specific bioactive factors interleukin‐2 and chemokine ligand 1 improves Treg viability, suppressive phenotype, and function, and attracts to the structure CCR8 + T‐cells enriched with anti‐inflammatory subpopulations, including Tregs, from human peripheral blood. Furthermore, these findings are applicable to 3D bioprinting. Co‐axial printing of murine pancreatic islets with human natural and induced Tregs protects the islets from xenoresponse upon co‐culture with human peripheral blood mononuclear cells. This establishes the co‐encapsulation of Tregs by co‐axial 3D bioprinting as a valid option for providing local immune protection to allogeneic cellular transplants such as pancreatic islets. Abstract : Encapsulation of regulatory T‐cells (Tregs) could provide local immune protection for co‐encapsulated cells such as pancreatic islets, thereby preventing rejection. Human natural and induced Tregs are successfully encapsulated in alginate‐gelatin methacryloyl hydrogel supplemented with interleukin‐2 and chemokine ligand 1. Furthermore, co‐axial bioprinting of murine islets with human Tregs protects the islets from xenoresponse upon co‐culture with human immune cells.